Safety and feasibility of oral carbohydrate consumption before cesarean delivery on patients with gestational diabetes mellitus: A parallel, randomized controlled trial. Issue 4 (5th January 2021) - Liu, Ningning; Jin, Ying; Wang, XiaoJuan; Xiang, Zhenzhen; Zhang, Le; Feng, Suwen
Abstract: Aim: To investigate the safety and feasibility of taking low‐concentration carbohydrate solution at 2 h before induction of anesthesia for gestational diabetes mellitus (GDM) patients. Methods: GDM patients undergoing cesarean section were randomly assigned to experimental group ( n = 43) and control group ( n = 42). Two hours before induction of anesthesia, participants in experimental group orally received 300 mL low‐concentration carbohydrate solution, while those in control group received equivalent warm water. Blood glucose and serum insulin were measured at 2 h before induction of anesthesia, right before induction of anesthesia, and the morning of postoperative day 1. Neonatal blood glucose level was monitored at birth. Maternal gastrointestinal function and well‐being were assessed perioperatively. Results: The levels of blood glucose and serum insulin right before induction of anesthesia in the experimental group were significantly higher than those in the control group. There were four cases with hypoglycemia in the experimental group and 19 cases in the control group right before induction of anesthesia (9.3% vs 45.2%, p < 0.001). The incidence of neonatal hypoglycemia was 2.3% in the experimental group and 7.1% in the control group with no significance. Hunger score of the participants between the two groups right before induction of anesthesia was significantly different. No aspiration, nausea, and vomiting occurred in both groups before, during, and after surgery. No significant difference was found in the time to the first flatus and abdominal distension between the two groups. Conclusion: Taking low‐concentration carbohydrate solution is safe and feasible for patients with GDM undergoing elective cesarean section.